2016
DOI: 10.1177/1753495x16653548
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya disease in pregnancy and delivery planning: A case series and literature review

Abstract: Moyamoya disease is a rare condition characterized by stenosis or occlusion of the intracranial internal carotid arteries leading to the development of fragile collateral vessels. Disruption of these vessels can lead to both ischemic and hemorrhagic strokes. As such, these patients are sensitive to changes in intracranial pressure and pose a challenge in pregnancy and delivery planning. Two cases of a parturients with moyamoya disease are presented, and the literature regarding safe method of delivery in simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Management of Moyamoya disease includes medical treatment for hypertension, vasodilators, anticonvulsants, surgical treatment involving revascularisation surgery, or a combination of these [2,5]. A recent case series has reported that pregnancy-related stroke secondary to Moyamoya disease is related to gestational age, with the highest risk of intracranial haemorrhage occurring antenatally, particular at or greater than 24 weeks [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Management of Moyamoya disease includes medical treatment for hypertension, vasodilators, anticonvulsants, surgical treatment involving revascularisation surgery, or a combination of these [2,5]. A recent case series has reported that pregnancy-related stroke secondary to Moyamoya disease is related to gestational age, with the highest risk of intracranial haemorrhage occurring antenatally, particular at or greater than 24 weeks [6].…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard for method of delivery in patients with Moyamoya disease [2]. The aim is to maintain haemodynamic stability by controlling blood pressure, managing pain to minimise hyperventilation causing hypocapnia and cerebral vasoconstriction, and careful fluid management [2,5]. Caesarean section with epidural anaesthetic can be safe, as can an uncomplicated instrumental vaginal delivery [2,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation